Perception of social competences during the SARS-COV-2 pandemic during remote science among students of the Bialska Academy of Applied Sciences John Paul II - Sandra Tur; Olga Anna Filipiak (Rozprawy Społeczne)
Abstract The aim of the article is to analyze the perception of social competences among students of the ABNS during the SARS-CoV-2 pandemic during distance learning.